La Crisis de los PIIGS y la Recuperación de Irlanda: Un Análisis Descriptivo (2019)
Some analysts point out that the economic crisis of the group of countries known as the PIIGS, which in turn contracted GDP growth in the eurozone, was an expansion of the North American mortgage crisis of 2008. However, these analyzes are unaware of the macroeconomic imbalances that these countries were accumulating years ago and that sooner or later they would take the euro to its worst crisis, since its appearance in 1999.On the other hand, within the group of PIIGS, stands out the Irish economy that in 2015 registered an economic growth of 25.6%, which has generated some accelerated appreciations that indicate that the figures of the island are the result of the costly financial rescues and the austerity policies applied, as a condition for receiving such rescues.In the group of PIIGS, it is important to understand that the accumulated economic problems are related to their entry into the eurozone; and in the Irish case, the análisis of so me macroeconomic indicators allow us to conclude that fiscal policy, on the one hand, was contractive and on the other, expansive, with more weight on the expansive part, which is currently supporting the recovery of the socalled “Tigre Celta”.